Optimal Portfolio Analysis of Kelly Criteria and Markowitz Models Using the Lagrange Multiplier Method in the Foreign Exchange - Sukono, Endang Rusyaman, Evi Sulviah Ningsih, Kalfin (International Journal of Advanced Science and Technology, 2020)
The proportion or weight invested in each exchange rate in the formation of a portfolio is investigated in this section. Portfolio optimization based on the Mean-Variance model and the Markowitz model aims to obtain an efficient portfolio weight composition by maximizing return expectations and minimizing the level of risk as measured by variance. Based on the results of the analysis it was found that the optimal portfolio of Mean-Variance models composed of five foreign exchange rates was a portfolio with a weight vector composition , respectively for USD, SAR, KWD, JPY and SGD exchange rates. This optimal portfolio composition produces a return of 0.0287747659 and a return variance of 0.0034697423. While the optimal portfolio of Kelly criteria models composed of five foreign currencies is a portfolio with a weight vector composition = (0.08947 0.08945 0.06649 0.09242 0.00049), respectively for USD, SAR, KWD, JPY and SGD exchange rates. This optimal portfolio composition produces an expected return of 0.010526773 and a variance of 0.000493281